2019
DOI: 10.3390/v11030237
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Herpesvirus Type 4 (BoHV-4) Vector Delivering Nucleocapsid Protein of Crimean-Congo Hemorrhagic Fever Virus Induces Comparable Protective Immunity against Lethal Challenge in IFNα/β/γR−/− Mice Models

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is the causative agent of a tick-borne infection with a significant mortality rate of up to 40% in endemic areas, with evidence of geographical expansion. Due to a lack of effective therapeutics and control measures, the development of a protective CCHFV vaccine remains a crucial public health task. This paper describes, for the first time, a Bovine herpesvirus type 4 (BoHV-4)-based viral vector (BoHV4-∆TK-CCHFV-N) and its immunogenicity in BALB/c and protection po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Additionally, CCHFV produces severe disease in STAT-1 −/− mice and mice lacking both the IFN-I receptor and IFN-gamma receptor (IFNAGR −/− ). These animals have deficiencies in both IFN-I and type II interferon (IFN-γ) signaling [78,79]. We recently developed a novel murine system by exploiting an antibody against IFN-I receptor A (MAR1-5A3) that was previously shown to produce severe disease models with other unrelated viruses [80,81].…”
Section: Small Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CCHFV produces severe disease in STAT-1 −/− mice and mice lacking both the IFN-I receptor and IFN-gamma receptor (IFNAGR −/− ). These animals have deficiencies in both IFN-I and type II interferon (IFN-γ) signaling [78,79]. We recently developed a novel murine system by exploiting an antibody against IFN-I receptor A (MAR1-5A3) that was previously shown to produce severe disease models with other unrelated viruses [80,81].…”
Section: Small Animal Modelsmentioning
confidence: 99%
“…Protective efficacy of various CCHFV vaccines including DNA, MVA-vectored and adenovirus-vector vaccines have been reported in IFNAR −/− mice, including those on the 129 and C57BL/6 backgrounds [82,107,112,113]. Another group reported protective efficacy of a vaccine expressing N on a Bovine herpesvirus type 4 vector in mice lacking both type I and type II interferon receptors [79]. Rodriguez, et al reported the protective efficacy of a recombinant a vesicular stomatitis virus (rVSV) expressing the glycoproteins in STAT-1 −/− mice from lethal challenge [86].…”
Section: Countermeasure Developmentmentioning
confidence: 99%
“…Additionally, it has been documented that antibodies produced against this protein have no neutralizing effect on the virus. However, despite the lack of neutralizing antibodies, vaccination using different expression platforms delivering the S segment sufficiently stimulated the immune response to protect the challenged mice models [5,6,7,8]. To clarify this phenomenon, one study documented that vaccines based on this gene elicited balanced Th1 and Th2 responses, which resulted in protection in genetically modified mice models against lethal doses [9].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure was repeated two more times. The virus was titrated between each passage using a standard TCID50 assay in SW-13 cells [28]. RNA extraction from the virus-infected aqueous phase of the cell cultures was performed by QIAamp Viral RNA Mini Kit (QIAGEN, Germantown, MD, USA) according to the manufacturer's instructions.…”
Section: Virus and Analysis Of Growth Kinetics In The Cell Linesmentioning
confidence: 99%
“…The cycling conditions were as follows: cDNA synthesis at 50 • C for 10 min, initial denaturation at 95 • C for 2 min, and 40 cycles of denaturation at 95 • C for 5 s, and annealing/extension at 60 • C for 30 s. The primers and probe were targeting the nucleoprotein gene (small segment) as previously described [27]: qPCR-F (5 -GGACATAGGTTTCCGTGTCA-3 ), qPCR-R (5 -TCCTTCTAATCATGTCTGACAGC-3 ) and qPCR-probe (5 -FAM-AGAACAACTTGCCAATTACCAACAGGC-BHQ1-3 ). Standard linear plasmids were prepared by 10-fold dilutions equivalent to 2 × 10 3 to 2 × 10 8 copies/reaction mixture using pCD-N1 as the template [28]. The reactions were carried out in one step by a Rotor-Gene Q instrument (QIAGEN, Germantown, MD, USA) and all calculations were then transformed to log-based viral loads (copies/mL).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%